The role of nitrogen in leaf senescence of summer maize and analysis of underlying mechanisms using comparative proteomics. (April 2015) - Wei, Shanshan; Wang, Xiangyu; Zhang, Jiwang; Liu, Peng; Zhao, Bin; Li, Geng; Dong, Shuting
Highlights: Maize leaf senescence induces the degradation of senescence-associated proteins. Nitrogen-related senescence proteins regulated leaf senescence. Underlines the central role of nitrogen in delaying senescence in maize leaves. Abstract: Leaf senescence is associated with fundamental changes on the level of the proteome and it can be modulated by nitrogen. To determine the precise regulatory mechanisms underlying these effects, we conducted a comparative proteomics study using 2-dimensional gel electrophoresis and MALDI-TOF/TOF MS. Based on our study of the maize leaf proteome, leaf senescence induces complex responses including the degradation of 32 senescence-associated proteins that are involved in many biological processes, especially energy, metabolism and cell rescue, defense and virulence pathways. Although similar conclusions have been highlighted in other crops, this study filled the knowledge gap in maize leaf senescence. Moreover, we discovered, for the first time, 29 "nitrogen-regulated senescence proteins" had significant ( P ≤ 0.05) interaction term for nitrogen × stage. Although further study of nitrogen-related senescence proteins, such as 30S ribosomal protein, will be required to fully elucidate their complex functions, the surprising results in our study provide a new vision to research the relationship between nitrogen and senescence.